Co-production, new public governance and third sector social services in Europe - Victor Pestoff (Ciências Sociais Unisinos)
Many countries in Europe are searching for new ways to engage citizens and involve the third sector in the provision and governance of social services in order to meet major demographical, political and economic challenges facing the welfare state in the 21st century. Co-production provides a model for the mix of public service agents and citizens who contribute to the provision of a public service. New Public Governance (NPG) puts much greater emphasis on citizen participation and third sector provision of social services than either traditional public administration or New Public Management. Co-production is a core element of NPG that promotes the mix of public service agents and citizens who contribute to the provis ionof a public service. This paper explores the implications of two comparative studies of paren tparticipation in preschool services in Europe. They observe that citizen participation clearly varies between different providers of social services, as too does client and staff influence. This empirical overview concludes that some third sector providers can facilitate greater citizen participation, while a 'glass ceiling' for participation exists in municipal and for-profit preschool services. These findings can contribute to a better understanding of the emerging paradigm of New Public Governance.